2019
DOI: 10.21608/pssjn.2019.66464
|View full text |Cite
|
Sign up to set email alerts
|

Assessment Of Nurses' Performance Regarding Caring Of Patients On Anticoagulant Therapy In Port-Said Hospitals

Abstract: Background: anticoagulants are high-risk drugs so it is very important to monitor the patients receiving anti-coagulant therapy. Aim: assess the nurses' performance regarding caring of patients on anticoagulant therapy in Port Said Hospitals. Subjects and Method: a descriptive research design was used A convenient sample of 130 nurses at three hospitals affiliated to Ministry of Health (Port-Said General Hospital, Port-Fouad General Hospital and El-Zohor Central Hospital) at Port-Said governerate were recruite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
1
5
1
Order By: Relevance
“…Therefore, it is required to emphasize on effective decisions for anticoagulation therapy policy and current practical guidelines. [ 18 ] In line with our study, the study conducted by Cheragi et al . in Iran found that the nurses’ practice regarding high-risk drugs such as warfarin was of poor quality.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Therefore, it is required to emphasize on effective decisions for anticoagulation therapy policy and current practical guidelines. [ 18 ] In line with our study, the study conducted by Cheragi et al . in Iran found that the nurses’ practice regarding high-risk drugs such as warfarin was of poor quality.…”
Section: Discussionsupporting
confidence: 92%
“…also highlighted the deficiency in nursing practice in their research. [ 18 ] The samples of our study were cardiovascular nurses and it was expected these nurses had proper practice about warfarin as a main drug of patients with heart diseases, but the results showed otherwise. Therefore, it is probably anticipated that the quality of practice could be even worse among general nurses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations